DYNAMIC OF K-POP AND SOCIAL MEDIA POTENTIAL FOR FAN ACTIVITIES: A COMPREHENSIVE REVIEW - Irmawan Rahyadi; Nadia Novita Risky; Rara Andica Oyza Sativa; Matthew Austin Naibaho (Sean Institute, 2022)
In today's digital era, social media in particular, allows us to get and share informations very quickly. Not only information but also entertainment needs that we can get from various countries, K-pop is one of them. K-pop is currently spread in almost the entire global music world, there are many fans from all over the wolrd. This phenomenon, which is usually called the Korean Wave, has finally resulted in an online-based fan community whose members like K-pop, or commonly called K-Pop Fandom or K-Pop Stan. This study aims to determine the characteristics of K-pop fandom on social media in supporting their idols and how they interact with other fans or with their favorite idols. As a literature review this study review previous reasearch with a certain set of processes. The results found that social media has a major impact on K-pop fandom starting from how they communicate, identity, happiness, sharing interests, building interpersonal relationships among fans. There, they have an online fandom hierarchy with different fan activities and roles. The way K-pop fandom interacts to get closer to their idols is to become an authentic K-pop fan or have an impact on their lives after getting to know K-pop.